Towards Situation-specific Software Support for Cross-organizational Design Thinking Processes - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 5th International Workshop on Software-intensive Business (IWSiB'22))
Due to the increasing influences of a VUCA world, design thinking workshops have been established as a standard technique to build solutions according to uncertain customer needs. Concerning the ongoing pandemic and rising development of solutions across organizations, more and more workshops were conducted online with software support. However, existing software tools insufficiently address the different workshop situations in terms of the process (i.e., fixed tasks to conduct), the place (e.g., static online whiteboards), and people (i.e., synchronous working of all stakeholders). Therefore, we propose a design science study to develop a situation-specific software support that can be configured with flexible development processes, different places, and task-related people. Based on practical experience in existing research projects, we derive the initial design requirements and map them to a set of design principles. Out of that, we design a concept with its implementation as a software tool and point out open challenges.
Keywords: design thinking; situation-specific; cross-organizational; software support

Gamification-based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems (MODELS 2022))

Comparative Evaluation of AR-based, VR-based, and Traditional Basic Life Support Training - Yigitbas, Enes; Krois, Sebastian; Renzelmann, Timo; Engels, Gregor (Proceedings of the 10th International Conference on Serious Games and Applications for Health (SeGAH'22))

Human-in-the-Loop Large-Scale Model Transformations with the VICToRy Debugger - Weidmann, Nils; Yigitbas, Enes; Anjorin, Anthony; Srivastava, Ankita; Jose, Jane (The Journal of Object Technology)

Competitive Routing in Hybrid Communications Networks and Message efficient SetCover in AdHoc Networks - Kolb, Christina

Zu den Auswirkungen von Big Data auf personalisierte Angebote in digitalen Märkten - eine wettbewerbspolitische Analyse - Sowinski, Olivia

Zu den Vor- und Nachteilen von Luftfahrtallianzen - Eine wettbewerbspolitische Perspektive auf den Alleingang von Emirates - Schmidt, Thomas

An Economic Analysis of Mergers and Aquisitions - The case of Facebook and WhatsApp - Yeboah, Amoabeng

A self-stabilizing Hashed Patricia Trie - Knollmann, Till; Scheideler, Christian (Information and Computation)
While many research in distributed computing has covered solutions for self-stabilizing computing and topologies, there is far less work on self-stabilization for distributed data structures. However, when peers in peer-to-peer networks crash, a distributed data structure may not remain intact. We present a self-stabilizing protocol for a distributed data structure called the Hashed Patricia Trie (Kniesburges and Scheideler WALCOM'11) that enables efficient prefix search on a set of keys. The data structure has many applications while offering low overhead and efficient operations when embedded on top of a Distributed Hash Table. Especially, longest prefix matching for x can be done in O(log |x|) hash table read accesses. We show how to maintain the structure in a self-stabilizing way, while assuring a low overhead in a legal state and an asymptotically optimal memory demand of O(d) bits, where d is the number of bits needed for storing all keys.

Untersuchung von kleinskaligen Flüssigkeitselementen auf mikrostrukturierten Packungsoberflächen - Dechert, Christopher; Kenig, Eugeny

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik. 2. Auflage)

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Sichere Räume, reparative Kritik. Überlegungen zum Arbeiten mit verletzendem Material - Shnayien, Mary (Zeitschrift für Medienwissenschaft)
Medienwissenschaftliche Forschung zu tagesaktuellen Themen ist oft damit konfrontiert, große Mengen an antisemitischem, rassistischem, misogynem, verschwörungstheoretischem Material sichten und analysieren zu müssen, dessen Verletzungspotential auch die jeweiligen Forscher_innen negativ affiziert. Der Beitrag fragt nach möglichen Bewältigungsstrategien, mit denen sich zu verletzendem Material forschen lässt, und die eine wirkungsvolle Kritik desselben ermöglichen, ohne als Forscher_in in die vom Material ausgehenden negativen Affekte und Epistemologien verwickelt zu werden.

Lab Books - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

Die unsicheren Kanäle. Negative und queere Sicherheit in Kryptologie und Informatik - Shnayien, Marie-Luise

Sozialistische Berufswahl und Nachwuchslenkung in der DDR - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Der vorliegende Beitrag befasst sich mit der Berufswahl in der ehemaligen DDR. Hier wurde von einer "gelenkten Berufswahl" gesprochen. Dabei galten alle Berufe als gleichwertig. "Sozialistische Berufswahl" wurde als pädagogisches Programm und als freie Berufswahl betrachtet. Dies gilt es genauer zu erörtern. Grundlage sind Beiträge, die in der Berufsbildung zwischen 1950 und 1979 erschienen sind.
Keywords: Berufswahl; DDR

Resilienz durch Integration freiwilliger Helfer*innen in den Katastrophenschutz: organisationale und (forschungs-)politische Perspektiven - Hälterlein, Jens; Kaufmann, Stefan (Resilienz als Prozess)

Molière, dramaturge de la société de cour

Absence of ground states in the renormalized massless translation-invariant Nelson model - Dam, Thomas Norman; Hinrichs, Benjamin (Reviews in Mathematical Physics)
We consider a model for a massive uncharged non-relativistic particle interacting with a massless bosonic field, widely referred to as the Nelson model. It is well known that an ultraviolet renormalized Hamilton operator exists in this case. Further, due to translation-invariance, it decomposes into fiber operators. In this paper, we treat the renormalized fiber operators. We give a description of the operator and form domains and prove that the fiber operators do not have a ground state. Our results hold for any non-zero coupling constant and arbitrary total momentum. Our proof for the absence of ground states is a new generalization of methods recently applied to related models. A major enhancement we provide is that the method can be applied to models with degenerate ground state eigenspaces.